Profil Pengepul Bunga Jepun Keringdi Kota Denpasar - I KETUT YOGA SUAMBARA; NI WAYAN PUTU ARTINI; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Profile Of Dried Jepun Flower Collectors In Denpasar City This study aims to determine the profile of dried Japanese flower collectors in Denpasar City, marketing channels and constraints faced. The location of the study was in the city of Denpasar determined purposively. The population of this study is dried Japanese flower collectors who are looking for flowers to go around. The sampling technique uses the census method. The data analysis method used in this research is descriptive method. The results of this study show that the average collectors are men aged 27 to 41 with an average education for six years and all collectors come from outside the island of Bali. Collectors only have one marketing channel, that is, people who collect dried Japanese flowers sell dried Japanese flowers to collectors, then collectors sell them to traders and large traders buy dried Japanese flowers to collectors. The constraints faced by collectors are two constraints, namely the technical aspects and economic aspects.